2015
DOI: 10.1007/s10295-014-1580-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel thermophilic phospholipase B from Thermotoga lettingae TMO: applicability in enzymatic degumming of vegetable oils

Abstract: A novel phospholipase B (TLPLB) from Thermotoga lettingae TMO has been cloned, functionally overexpressed in Escherichia coli and purified to homogeneity. Gas chromatography indicated that the enzyme could efficiently hydrolyze both the sn-1 and sn-2 ester bonds of 1-palmitoyl-2-oleoyl phosphatidylcholine as phospholipase B. TLPLB was optimally active at 70 °C and pH 5.5, respectively. Its thermostability is relatively high with a half-life of 240 min at 90 °C. TLPLB also displayed remarkable organic solvent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…This TLPLB was shown to be more stable in non-polar than polar organic solvents. Indeed, after incubation in hydrophobic organic solvents, TLPLB retained 91% to 161% of its phospholipase activity, while in hydrophilic solvents its residual activity was only 10% to 38% [ 104 ]. Recently, the two PLA 2 s from pancreas [ 79 ] and intestine [ 80 ] of the common stingray were shown to retain 100% of their activity in incubations with polar organic solvents; increased activity was even observed in the presence of ethanol and acetonitrile (by 12% to 23%).…”
Section: Lipase and Phospholipase In Biocatalysismentioning
confidence: 99%
“…This TLPLB was shown to be more stable in non-polar than polar organic solvents. Indeed, after incubation in hydrophobic organic solvents, TLPLB retained 91% to 161% of its phospholipase activity, while in hydrophilic solvents its residual activity was only 10% to 38% [ 104 ]. Recently, the two PLA 2 s from pancreas [ 79 ] and intestine [ 80 ] of the common stingray were shown to retain 100% of their activity in incubations with polar organic solvents; increased activity was even observed in the presence of ethanol and acetonitrile (by 12% to 23%).…”
Section: Lipase and Phospholipase In Biocatalysismentioning
confidence: 99%
“…DOI: 10.1159/000491698 beyond a few hours [Fu et al, 2015;Kato et al, 2010;Wei et al, 2015;Wemheuer et al, 2013]. PLP_2.9 also showed acyltransferase activity since the addition of methanol to the enzymatic reaction mixture containing PC resulted in the formation of fatty acid methyl esters.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wei et al [2015] reported the characterization of a thermophilic phospholipase from Thermotoga lettingae TMO that they proposed for use in the enzymatic degumming of vegetable oils. Similarly, the high thermal stability of PLP_2.9 warrants further studies aimed toward the potential applicability of PLP_2.9 to this process.…”
Section: Discussionmentioning
confidence: 99%
“…After citric acid treatment, the oil was then degummed by rPLB. Enzymatic hydrolysis reduced the phosphorus content of peanut oil from 91.8 to 3.7 mg/kg within 3 h. The PLBs from P. fluorescens BIT-18 and T. lettingae reduced the phosphorus content to levels below 10 mg/kg, yielding levels of 4.96 mg/kg (soybean oil), 3.54 mg/kg (peanut oil) and 4.9 mg/kg (rapeseed oil) or 4.7 mg/kg (soybean oil), 3.2 mg/kg (peanut oil), and 2.2 mg/kg (sunflower seed oil), respectively [19,20]. However, limited studies have investigated the use of PLB in enzymatic degumming.…”
Section: Application Of Rplb In Peanut Oil Degummingmentioning
confidence: 99%
“…Therefore, a novel enzymatic procedure utilising PLBs as biocatalysts has been developed for the production of GPC. In addition, although PLBs from Pseudomonas fluorescens BIT-18 and Thermotoga lettingae have been used to degum soybean, peanut, rapeseed and sunflower seed oils [19,20], few studies have investigated the use of PLB for enzymatic degumming processes. In the present study, the plb 2 gene (hereafter referred to as plb) from S. cerevisiae was cloned and expressed in Pichia pastoris GS115, and recombinant PLB (rPLB) was purified, characterised and tested for the production of GPC and peanut oil degumming.…”
Section: Introductionmentioning
confidence: 99%